2011
DOI: 10.1007/s00425-011-1460-6
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in xylem vessel diameter and embolisms in grafted apple trees of differing rootstock growth potential in response to drought

Abstract: We investigated responses of plant growth rate, hydraulic resistance, and xylem cavitation in scion-rootstock-combinations of Malus domestica L. cv. Honeycrisp scions grafted onto a high-shoot vigor (HSV) rootstock, (semi-dwarfing Malling111), or onto a low-shoot vigor (LSV) rootstock, (dwarfing Budagovsky 9), in response to substrate moisture limitation. Adjustments in xylem vessel diameter and frequency were related to hydraulic resistance measurements for high- versus low- vigor apple trees. We observed a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 37 publications
0
29
0
1
Order By: Relevance
“…The use of an index can be a valuable metric to examine larger data sets that are compiled of several species to look for generality in vulnerability patterns (Zanne et al, 2010). The potential of vessel vulnerability during water stress was determined using methods from Carlquist (1977) where vulnerability index (VI) = VD/VF, where VD is vessel diameter (μm), and VF is VF (N/mm −2 ) (Gonçalves et al, 2007; Bauerle et al, 2011; Aref et al, 2013). To parse seasonal differences in vessel traits and vulnerability, three equal concentric rings were overlaid on the cross section to delineate the first, middle, and last rows of vessels to represent the seasonal transition in vessel development from early to late season.…”
Section: Methodsmentioning
confidence: 99%
“…The use of an index can be a valuable metric to examine larger data sets that are compiled of several species to look for generality in vulnerability patterns (Zanne et al, 2010). The potential of vessel vulnerability during water stress was determined using methods from Carlquist (1977) where vulnerability index (VI) = VD/VF, where VD is vessel diameter (μm), and VF is VF (N/mm −2 ) (Gonçalves et al, 2007; Bauerle et al, 2011; Aref et al, 2013). To parse seasonal differences in vessel traits and vulnerability, three equal concentric rings were overlaid on the cross section to delineate the first, middle, and last rows of vessels to represent the seasonal transition in vessel development from early to late season.…”
Section: Methodsmentioning
confidence: 99%
“…This mechanism is likely to be conserved in woody plants. Indeed, several reports have shown that water availability induces modification of vessel diameter in Ulmus genotypes (Solla and Gil, 2002a), Populus genotypes (Fichot et al, 2009), Malus domestica (Bauerle et al, 2011) and V. vinifera (Lovisolo and Schubert, 1998). In addition, the degree of developmental plasticity of the xylem in response to water availability is a function of plant genetic makeup (Fichot et al, 2009).…”
Section: Factors Influencing Xylem Vessel Sizementioning
confidence: 99%
“…Correlation between vessel diameter, maximal hydraulic conductivity in roots and trunks of rootstocks and their ability to confer vigor to scions were observed in many perennial crops such as Prunus spp. (Gonçalves et al, 2007; Tombesi et al, 2010b; Tombesi et al, 2011), Malus spp., (Bauerle et al, 2011), and Olea spp. (Trifilò et al, 2007).…”
Section: Factors Influencing Xylem Vessel Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Rootstocks may provide drought resistance by altering processes other than stomatal closure. In apple rootstocks, drought resistance has been attributed to increased hydraulic conductance, recovery from embolisms in the xylem, and shift in assimilate partitioning to root growth (Atkinson et al, 1999;Bauerle et al, 2011;Cohen et al, 2007). Hydraulic conductance was 66% more in 'Gala' than 'Fuji' stems on any rootstock (Tworkoski and Fazio 2015a).…”
Section: Introductionmentioning
confidence: 99%